Should Household Consumption and Expenditures Surveys (HCES) be used for nutritional assessment and planning? - Murphy, Suzanne; Ruel, Marie T.; Carriquiry, Alicia (SAGE Publications, 2012)
Household Consumption and Expenditures Surveys (HCES) are routinely conducted in several countries on nationally representative samples, often on a regular basis. The HCES have been considered as a potential alternative to more expensive surveys of individuals' food intakes for use in nutritional assessment and in planning programs such as food fortification. HCES gather information on household food availability (purchased, produced, or received as gifts) and use over a given period of time, often the past week or month.To discuss the potential usefulness of HCES consumption data for nutritional assessment and planning for populations of households and individuals within the households.There are several limitations to the HCES, most notably the difficulty of estimating the intrahousehold allocation of foods and therefore of quantifying the actual food intake of individual household members. Another concern is the lack of information on the variability of consumption over time, making it difficult to estimate the distribution of usual consumption, and thus the prevalence of nutrient inadequacies or excesses. Other potential limitations might be addressed by improvements to the HCES questionnaires, such as including information on foods that are available but not consumed and those that are consumed outside the home. Research is needed to better understand both the strengths and the weaknesses of the HCES data when used to assess and plan intakes at the household and individual levels